Epstein‐Barr virus‐associated smooth muscle tumors after lung transplantation. Issue 3 (27th March 2019) - Hirama, Takashi; Tikkanen, Jussi; Pal, Prodipto; Cleary, Sean; Binnie, Matthew
Abstract: Background: Recipients of solid organ transplants are prone to various complications that are seldom encountered in immunocompetent individuals. Post‐transplant lymphoproliferative disorder (PTLD) is the best known and commonest Epstein‐Barr Virus (EBV)‐associated malignancy post solid organ transplant. EBV‐associated smooth muscle tumors (EBV‐SMT) including leiomyomas and leiomyosarcomas are rare and much less studied than PTLD. We recently encountered two cases of EBV‐SMT post lung transplantation and here we summarize their clinical features and course together with a literature review. Method: Clinical data and treatment details of two patients who developed EBV‐SMT were reviewed and retrieved up to December 31, 2017. English literature was searched through the PubMed database from 1965 to 2017 for studies of the association between lung transplant and EBV‐SMT. Results: The incidence of PTLD is higher among lung transplant recipients compared to kidney transplant recipients, an observation that has been attributed to stronger immune suppression in the lung patients. EBV‐SMT showed a higher incidence among kidney recipients than among lung recipients, suggesting that the degree of immunosuppression may be a less important factor in the development of EBV‐SMT. EBV‐SMT has most often been seen among lung transplant recipients with EBV mismatch. Conclusions: Because EBV‐SMT is a rare tumor, its incidence, risk factors, and optimal management have not been well‐defined and further study is needed.